Exploring the impact of ChatGPT: conversational AI in education - Bettayeb, Anissa M.; Abu Talib, Manar; Sobhe Altayasinah, Al Zahraa; Dakalbab, Fatima (Frontiers in Education, 2024)
This research paper presents a systematic literature review that explores the impact of integrating ChatGPT in education. Analyzing several scientific research articles published between 2022 and 2023, the study addresses four key research questions: the benefits and challenges of ChatGPT, its influence on student engagement and learning outcomes, ethical considerations and safeguards, and the effects on educators and teachers. The findings highlight several advantages of ChatGPT, including personalized assistance, enhanced learning experiences, and the opportunity for students to explore AI technology. Additionally, the paper identifies benefits of using ChatGPT in education, including enhanced learning and improved access to information. However, challenges such as biases in AI models and the need for ethical considerations are highlighted, emphasizing the importance of transparency and accountability in deployment. Challenges related to misinformation, human supervision, and potential misuse must be addressed to ensure the integrity and quality of educational content. The research reveals that ChatGPT positively impacts student engagement by providing tailored responses, prompt feedback, and quick access to information, leading to improved learning outcomes and the development of critical thinking skills. Ethical considerations and safeguards, such as clear guidelines, human supervision, privacy protection, and user education, are crucial to ensure the responsible and ethical use of ChatGPT in education. Moreover, the integration of ChatGPT brings about a shift in the role of educators from content delivery to facilitation and guidance. This transformation allows for personalized and differentiated learning, promotes inquiry and questioning skills, and requires educators to monitor student usage while addressing ethical considerations. By addressing challenges, establishing ethical guidelines, leveraging the strengths of ChatGPT, and recognizing the vital role of human educators, educational institutions can harness the advantages of ChatGPT to enhance student engagement, improve learning outcomes, and foster responsible and ethical use of AI technology in education. In doing so, they can create a dynamic learning environment that prepares students for future challenges.